2017
DOI: 10.1093/ntr/ntx215
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge and Credibility Perceptions of the FDA as a Tobacco Regulator

Abstract: This study is the first to show nationally representative estimates of both knowledge and credibility of the FDA as a tobacco regulator. Our research shows further that knowledge of the FDA's tobacco regulatory roles is likely to be an important factor related to perceived credibility of the FDA. Increasing the public's knowledge of the FDA's roles may enhance the agency's credibility, which can improve public reception to messages and regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Moreover, information on the FDA’s regulatory roles also resulted in a higher perceived knowledge of what the FDA does. Previous research has shown that the knowledge of FDA roles in regulating tobacco is strongly associated with perceived credibility of the organization [ 11 ]. Knowledge also plays a role in persuasion and can influence attitude change even in the absence of actual change in information or knowledge [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, information on the FDA’s regulatory roles also resulted in a higher perceived knowledge of what the FDA does. Previous research has shown that the knowledge of FDA roles in regulating tobacco is strongly associated with perceived credibility of the organization [ 11 ]. Knowledge also plays a role in persuasion and can influence attitude change even in the absence of actual change in information or knowledge [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Kowitt et al, (2017) found that only 43% of US adults reported trust in the federal government and that trust in FDA was moderate (62%) but lower than trust in the CDC (65%) [ 5 ]. Research also shows low public awareness of FDA’s tobacco regulatory and communication roles [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…27 However, FDA has reduced the visibility of the FDA logo and focused on branding their campaigns with The Real Cost , This Free Life , Fresh Empire , and more recently Every Try Counts . Yet, FDA is perceived as moderately credible as a tobacco regulator, 28 with 95% name recognition among adults in the US. 29 Given their credibility as an agency and high name recognition, more prominent FDA source attribution may improve campaigns by increasing the credibility of the campaign messages.…”
Section: Fda Source and Credibilitymentioning
confidence: 99%
“…8-11 In a focus group study with 41 US adults (24% self-identified as Black), Jarman et al 8 found that most participants were unaware of the FDA’s authority to regulate tobacco and expressed only partial trust in the FDA. Additionally, in a nationally representative survey of 4758 US adults (19.6% self-identified as Black), Schmidt et al 10 found that credibility perceptions of the FDA were higher among white respondents as compared to Black respondents.…”
mentioning
confidence: 99%
“…Whereas the trust gap indicated by the Schmidt et al study is not surprising, it does highlight the need for additional studies to describe the specific sources of distrust and to identify promising pathways for improving the perceived trustworthiness of the FDA among Black Americans. 10 Therefore, we conducted a qualitative study in Los Angeles, California, among Black community stakeholders employed in local organizations servicing a predominantly Black clientele. For the purpose of this paper, Black community stakeholders are defined as those with a vested interest or personal stake in activities that affect Black Americans residing in Los Angeles.…”
mentioning
confidence: 99%